Chile : subnational government finance. - World Bank. (Washington, D.C. : World Bank, 1993)
"Without significant and lasting sociopolitical change, Chile is not expected to join the club of developed nations. The present essay cont ains a thorough examination of the subnational government reforms that are needed to increase efficiency in the provision of basic health, edu cation, housing, and other semipublic or public services"--Handbook of Latin American Studies, v. 57.
Includes one folded color map.
Keywords: Intergovernmental fiscal relations -- Chile; Local finance -- Chile